ANALISIS MODEL PEMBELAJARAN ROLE PLAYING DALAM PEMBELAJARAN SEJARAH DI JENJANG SEKOLAH MENENGAH ATAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR REFLEKTIF - Ahmad Suandi; Taufik Nurhayati; Yusuf Budi Prasetya Santosa (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
Learning history among students is still stigmatized as boring. One of the reasons for this is that history teachers rarely make variations in the use of learning models. Role playing can be a learning model in history learning. This research uses the method of library research (library research) with documentation data collection techniques, and content analysis techniques (content analysis). The documents used in this research include notes, books, papers or scientific articles, textbooks and regulations. The purpose of this study was to see how the analysis of role playing learning models in history learning at the senior high school (SMA) level can foster reflective thinking skills? Based on the results of the study, the role playing learning model is not just a role play, but a learning model that encourages students to increase their social sensitivity by playing the characters in events, and also encourages reflective thinking skills as one of the higher order thinking skills in students.